Gestão democrática na rede estadual de ensino de Alagoas: percepções e perspectivas de uma política pública - Emiliano, Flávia Maria Monteiro de Lima (2008)
This dissertation has as objective to analyze the perceptions and perspectives about the public politics of implanted democratic management in the state net of education in Alagoas. The effectuation of this is glimpsed from a theoretical inquiry, of character pedagogical-politician, since it presents subsidies for the practical improvement of the pedagogical one in the school and the system of education; and, is characterized as politics for analyzing a process of implantation of one politics that if presents as an initiative in the education area, but that it keeps a restricted relation with the society. This research is supported theoretically in the conception of State defended by Gramsci when assuming that the State is a synthesis of society politics and civil society, State-coercion and private devices of hegemony. It detaches referring concepts to the democratic management, centralization, decentralization. It presents a historical briefing on the existing relation between centralization and decentralization. The possibility of decentralization of being able through the democratic management argues. It identifies three mechanisms that can make possible the democratic management: the Politician-Pedagogical Project, the Pertaining to school Advice and the Election for choice of pertaining to school managers. It describes the process of implantation of the democratic management in the state public net of education in Alagoas. It displays to finish this work the perceptions and perspectives that the involved ones in education of the State of Alagoas have regarding the public politics of implanted democratic management from 1999. It concludes detaching the advances reached for the state education although all the faced obstacles and the existing of social-political problems in the State. Key-Words: Democratic management, decentralization X centralization, Politician-Pedagogical Project, Pertaining to school Advice.